Award for work on water weed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The spread of water hyacinth (Eichornia crassipes) has had a devastating effect on many African lakes and waterways, disrupting transportation, depriving fish of essential oxygen and devastating communities by the resultant fall-off in economic...